Code Switching Used By The Characters In The One Fine Day Film - Puspadewi, I Dewa Ayu Tri; Maharani , Sang Ayu Isnu; Saientisna, Made Detriasmita (Innovative: Journal Of Social Science Research, 2024)
This research is entitled Code Switching Used by Characters in the One Fine Day film. Code switching is a term in the field of linguistics that refers to the use of more than one language or variations in conversation. This research aims to identify various types of code switching and explain how the code switching functions are used by the characters. Poplack's theories and Appel and Muysken theories were used as a basis for designing this research. This research uses primary data in the form of a film entitled "One Fine Day", The data collection methods used are documentation and observation with note-taking techniques to collect relevant data. This research reveals that in the film One Fine Day, there are three types of code switching used, namely tag switching, inter-sentential switching, and intra-sentential switching and also the six functions of code switching are found in this research.